If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = 7t + -31 Reorder the terms: 10 = -31 + 7t Solving 10 = -31 + 7t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-7t' to each side of the equation. 10 + -7t = -31 + 7t + -7t Combine like terms: 7t + -7t = 0 10 + -7t = -31 + 0 10 + -7t = -31 Add '-10' to each side of the equation. 10 + -10 + -7t = -31 + -10 Combine like terms: 10 + -10 = 0 0 + -7t = -31 + -10 -7t = -31 + -10 Combine like terms: -31 + -10 = -41 -7t = -41 Divide each side by '-7'. t = 5.857142857 Simplifying t = 5.857142857
| 379x+60=52 | | 132+4x+17+5x+5= | | -10x^2-101x-10=0 | | 8x^2=3-9x | | 3-4x=2(x-4)-7 | | -7(4x-2)+3.5=59.5 | | x+7-x=1 | | -6x-4=-26+5x | | 320-445X=15+10 | | 6(5x-12)=10x+8 | | 13+3(x-1)=9x | | 2x(y)=36 | | -12(k+4)= | | z+6+2z-4=z | | 16-36x+8x^2=0 | | -2x-2=-2 | | z+2+2z-6=20 | | -6+3x=2x-1 | | 579X+217=30 | | 14(p^2-1)=45 | | 6x-3=5x+2 | | 7(b+2)-46=2(b+10) | | .3(6z+10)= | | -3x+1=2x-14 | | 3x+9y=-6 | | 2-5(6v-1)=63 | | 17=3x-2x+6 | | y=12x+7 | | -3(-5z+12)= | | -x-1-6x=-36 | | -5(3x-2)+7=42 | | -(x+2)-5=-1 |